MUF250 : Principal study IV / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course focuses on singing or playing on an instrument in accordance to the students’ respective major and level of study. It emphasizes on development of singing/playing skills and musicality. Students are exposed to performance issues and stylistic interpretation of various pieces.